Factors Associated with the Incidence of Chronic Energy Deficiency (CED) in Pregnant Women in the Working Area of the UPT Health Center Inpatient Banding Agung in 2021 - Robiyati Robiyati; Siti Aisyah; Helni Anggraini (Institute of Computer Science (IOCS), 2022)
Background: Chronic energy deficiency is a condition where a pregnant woman suffers from a lack of food intake that lasts for a long time (chronic or chronic) which results in health problems, so that the increased nutritional needs during pregnancy cannot be met. The purpose of the study was to know the factors associated with the incidence of chronic energy deficiency in pregnant women in the work area of the Appeal Agung Inpatient Health Center in 2021. The research method was a quantitative research type of descriptive research using a cross sectional approach. using accidental sampling technique. The population in the study amounted to 245 people and the number of samples was 71 respondents. The results of the univariate analysis of respondents based on chronic energy deficiency were 48 people (67.6%), respondents based on economic status were 43 people (60.6%), respondents based on diet were 45 people (63.4%). Respondents based on knowledge amounted to 45 people (63.4%). The results ofthe bivariate analysis were a significant relation, honor between economic status with ap value of 0.000 <0.05, knowledge with ap value of 0.009 and eating patterns with ap value of 0.000 statistically proven. The conclusion is that there is a relationship between economic status, knowledge and eating patterns in the Working Area of the Great Appeal Inpatient Health Center in 2021. Suggestions for health workers Improve the quality of health services, especially services in antenatal care services. The need for counseling as often as possible about the nutrition of pregnant women to prevent chronic energy deficiency. Respondents based on diet were 45 people (63.4%).